Survival feature and trend of female breast cancer: A comprehensive review of survival analysis from cancer registration data - Dan-Dan Tang; Zhuo-Jun Ye; Wan-Wan Liu; Jing Wu; Jing-Yu Tan; Yan Zhang; Qun Xu; Yong-Bing Xiang (Breast)
To better understand global patterns, chronological changes, and international comparisons of female breast cancer survival, we reviewed published data from population-based cancer registries worldwide. Using PubMed, Embase, Web of Science, SEER, and SinoMed, a comprehensive literature search was conducted for female breast cancer survival from the population-based cancer registries through 31 December 2023. Observed, relative, and net survival rates and their corresponding age-standardized survival rates since the 1990s were collected and further stratified by prognostic factors. The prognosis of female breast cancer patients was favorable, with 5-year relative survival rates above 80 % in most regions. The trend in breast cancer survival showed annual increases in most countries but was accompanied by geographical disparities. The highest age-standardized 5-year relative survival rate was identified in the USA (2010–2014) at 90.2 %, while the lowest was in India (2010–2014) at 66.1 %. Overall, North America and Oceania had the best survival, and, for Europe, survival was worst in Eastern Europe. The survival in some Asian countries was disturbing. Younger age groups had a better prognosis than those aged 75 years and over. The lowest survival rates were observed in patients with distant metastatic and triple-negative breast cancer. Worldwide, there has been a steady improvement in female breast cancer survival. However, the survival gap between developed and developing countries has remained wide over the past 30 years. Differences in age, stage at diagnosis, and molecular subtype may explain some of the disparities, providing evidence for targeted management strategies.